Layanan Badan Penyelenggara Jaminan Sosial (BPJS) di Rumah Sakit Milik Pemerintah Provinsi Jawa Timur - M. Amir H. T.; Nakkok Aruan; M S Rifki (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2018)
BPJS service has been considered not maximal, even far from the ideals of the government as stipulated in the 1945 Constitution Article 28 and Act No. 23 of 1992 on Health. This research about BPJS service in two hospitals in East Java that is RSUD Dr. Saiful Anwar Malang and Dr. Soedono Madiun. The purpose of this study was to analyze BPJS service in both hospitals to the poor and incapable, research also to find out what kind of service BPJS patients in both hospitals. The study method uses a qualitative approach, with descriptive method. This method is done by interview and observation and direct survey to RSUD Dr. Saiful Anwar Malang and Dr. Soedono Madiun. The findings of this research conclude that BPJS services in both hospitals have not been effective since apart from the weak coordination between puskesmas and referral hospitals managed by BPJS, the coverage area of referral hospitals in both areas is so wide that they can not accommodate patients service BPJS.